Buriti oil emulsions as affected by soy protein isolate/high-methoxyl pectin ratio, oil content and homogenization pressure - Freitas, Mírian Luisa Faria (Array, 2020)
Research background. Emulsion technology is a suitable way of encapsulating, protecting and releasing hydrophobic bioactive compounds for application in food industries, but they are thermodynamically unstable systems. Good results have been achieved for emulsions stabilized by protein-polysaccharide complexes subjected to high-pressure homogenization. Improved stabilization of oil-in-water emulsions results from electrostatic complexes formed between proteins and polysaccharides at pH lower than the protein isoelectric point, which adsorb at the oil-water interface. In addition, polysaccharides contribute to emulsion stability by increasing viscosity of the continuous phase. The aim of this work is to investigate the production of carotenoid-rich buriti oil emulsions using soy protein isolate and high-methoxyl pectin as stabilizers. Experimental approach. Using a rotatable central composite experimental design, we assessed the effects of oil content, soy protein isolate/high-methoxyl pectin ratio and homogenization pressure on the stability, droplet size, electrical conductivity, electrical charge, microstructure and rheological behaviour of the emulsions.Results and conclusions. An optimized emulsion was produced with 28 % buriti oil, 55 % soy protein isolate, and homogenization pressure of 380·105 Pa. This emulsion was stable for at least seven days, presenting reduced average droplet size, low electrical conductivity and high modulus of negative charges. The mechanical spectra showed that the emulsion behaved as a viscoelastic gel under oscillatory, non-destructive shearing, whereas shearthinning behaviour took place under steady shear conditions.